Implementation of Healthy Food Patterns for the Millennial Generation Based on Local Food Diversification in the Agrotourism Area of Sembalun Bumbung Village - Nydia Alisa Putri; Nur Ilmiati; Dewi Putri Lestari; Achmad Fajar Natotama Sarjan; Muhammad Sarjan (Unram Journal of Community Service, 2024)
Sembalun Bumbung Agro-Tourism, a renowned destination on Lombok Island, is celebrated for its stunning natural beauty and its agricultural tourism, attracting local, national, and international visitors. Demographically, the population of Sembalun Bumbung, especially among the younger generation (millennials), is increasing. This demographic shift brings various impacts, including changes in dietary habits and agricultural activities, particularly in relation to food diversification. Therefore, it is crucial to educate the millennial community in the Sembalun Bumbung Agro-Tourism area about healthy eating patterns based on food diversification. The objectives of this initiative are: 1) To implement a balanced nutrition plan through a safe and healthy diet, and 2) To promote the daily consumption of foods rich in carbohydrates, proteins, fats, vitamins, and minerals in appropriate portions and schedules. Through these educational activities, it is anticipated that the knowledge of the community, especially among millennials, regarding healthy eating patterns will improve. Consequently, they will become agents of change in their village, fostering a habit of consuming a diverse range of local foods to enhance the overall health of the local community